Réponses

2014-03-14T21:05:08+01:00
a) 3-4x
b)3x-7
c) -2x2+3x-5
d) x2 + 3x -1
K = 5x - (2x-3)
K = 5x -2x + 3
K = 3x +3
L = 3x2 - (4x2 - x + 5)
L = 3x2 + 4x2 + x - 5)
L = 7x2 + x - 5
M = 4 + 6x -(-2x+7)
M = 4 + 6x + 2x -7)
M = 8x - 3
N = - 5x - ( -5x2 + x - 1)
N = - 5x + 5x2 - x + 1
N = 5x2 - 5x + 1
P = (-5x+7) - (8-3x) + x
P = -5x + 7 - 8 + 3x + x
P = -x - 1
Q = 3x - ( -5 + x) + (-3x + 3)
Q = 3x + 5 - x - 3x + 3
Q= -x + 8
R = -4x
² -(2x²-3x+1) + (-2x+3)
R =-4x
² - 2x² + 3x - 1 - 2x +3
R = -6x
² + x + 2